Theoretical Analysis Of Double Heterojunction Bipolar Transistors With Composite Collectors. - Goh , Yu Ling (2003)
A theoretical investigation of the DC current-voltage (I-V) characteristics and avalanche multiplication in GaInP/GaAs composite collector double heterojunction bipolar transistor (DHBTs) was performed using a physical one-dimensional analytical model developed based on the Ebers-Moll methodology. The concept of carrier transmission, reclection and tunneling at the potential barrier at the heterojunction was expounded in the analytical model.